Bilateral Serous Retinal Detachments Associated with Accelerated Hypertensive Choroidopathy - Yoshio Hirano; Tsutomu Yasukawa; Yuichiro Ogura (International Journal of Hypertension)
Purpose. We report a case of hypertensive choroidopathy with bilateral serous retinal detachments. Patient. A 50-year-old man underwent bilateral serous retinal detachments. Retinal arteriolar narrowing, vascular tortuosity, and arteriovenous nicking were identified in both eyes. The blood pressure was 206/125 mmHg. The patient was diagnosed with bilateral hypertensive choroidopathy and treated with oral antihypertensive treatment. Results and discussion. One month after antihypertensive treatment, the serous retinal detachments resolved and the visual acuity improved. A patient with those findings should be considered as having hypertensive choroidopathy and treated as soon as possible.